Laboratory methods for the in vitro study of drug metabolism - Crespi, Charles (Henry Stewart Talks, 2007)
Major classes of DMEs, Systems for laboratory study, Practical aspects, Examples of application, Obtaining high quality data, Minimizing artefacts
Archived at 2018/10/29